Community Empowerment through Structured Sports Programs to Support Mental and Emotional Health in India - Sai, Murari Monika; Gayatri, Kalaga V N S Anjanee (PT Agung Media Publisher, 2025)
Mental health challenges such as stress, anxiety, and sleep disturbances have become increasingly prevalent in Indian communities, especially among youth in semi-urban settings. While physical exercise is known to offer psychological benefits, its potential as a community-driven mental health intervention remains underutilized. This study explores the impact of structured sports programs in promoting psychological well-being through community empowerment using an Asset-Based Community Development (ABCD) approach. The intervention was implemented in a semi-urban region of Telangana, India, involving 120 participants and 30 trained youth facilitators. Community assets were mapped and mobilized to develop weekly sports sessions combined with group reflection activities. Mixed methods were used to evaluate outcomes: self-reported surveys on stress, sleep, and mood; qualitative reflection logs and participatory observation. The structure was rooted in ABCD principles to ensure sustainability and local ownership. Quantitative findings showed a 53% reduction in daily stress and a 44% improvement in sleep quality among participants. A substantial increase in group participation, emotional openness, and community involvement was also observed. Trained youth facilitators reported improved self-confidence and took active leadership roles in organizing sessions. The intervention led to the formation of a local taskforce, ensuring program continuity beyond institutional support. The program successfully reframed sports as a culturally appropriate tool for emotional expression and mental health awareness. It also fostered a cultural shift in how mental health is discussed within families and peer groups. Although self-reported data and short-term tracking limited generalizability, the results highlight the promise of scalable, community-owned, sports-based mental health strategies.